2014
DOI: 10.1586/14737175.2014.915742
|View full text |Cite
|
Sign up to set email alerts
|

The current role of mitoxantrone in the treatment of multiple sclerosis

Abstract: Mitoxantrone is an immunosuppressive drug approved for aggressive relapsing and progressive multiple sclerosis. In recent years, its use has decreased due to the risk of severe adverse events and the introduction of novel therapies, such as natalizumab or fingolimod. Mitoxantrone is effective in reducing inflammatory activity by decreasing the number of relapses and MRI lesions and simultaneously decreasing the worsening of disability. Apart from its role as a second/third-line therapy, some studies suggest it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 63 publications
0
14
0
4
Order By: Relevance
“…Although the results of the present study confirm previous concerns about a broad and prolonged use of MTX for the treatment of MS, some additional consideration are needed. It has already been suggested that, in the effort to guarantee MS patients with the best possible treatment to prevent the accrual of not reversible disability, particularly for patients with clinical subtypes that do not have yet valid therapeutic opportunities, MTX could still represent one the few chances available [24]. What it is still open to debate is how to use this drug.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results of the present study confirm previous concerns about a broad and prolonged use of MTX for the treatment of MS, some additional consideration are needed. It has already been suggested that, in the effort to guarantee MS patients with the best possible treatment to prevent the accrual of not reversible disability, particularly for patients with clinical subtypes that do not have yet valid therapeutic opportunities, MTX could still represent one the few chances available [24]. What it is still open to debate is how to use this drug.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 55% of patients had no evidence of disease activity at follow-up. Infectious complications occurred in 47% with no long-term morbidity and no deaths [16].…”
Section: Treatment Choices: Past and Present Experiencesmentioning
confidence: 92%
“…It is usually administered intravenously at a dose of 12 mg/m 2 every three months until a maximum total cumulative dose of 140 mg/m 2 has been reached, but this therapeutic regimen may vary. In recent years, use of MTX has decreased due to the risk of severe adverse events [16].…”
Section: Treatment Choices: Past and Present Experiencesmentioning
confidence: 99%
“…I dati di efficacia di alemtuzumab in pazienti con forma di malattia attiva [almeno una ricaduta clinica durante il trattamento con terapie di prima linea (IFNß e glatiramer acetato)] derivano invece dal trial MS-CARE II, che ha documentato una significativa riduzione del numero di ricadute cliniche e della progressione della disabilità (p <0,0001) nei pazienti trattati con alemtuzumab versus i pazienti randomizzati al trattamento con IFNß-1a [42]. Anche per mitoxantrone esistono evidenze di efficacia nei pazienti con forme molto attive di malattia, e tale farmaco è stato usato, in particolare prima dell'approvazione di fingolimod, natalizumab e alemtuzumab, sia come terapia di induzione nei pazienti attivi fin dall'esordio della malattia, ma soprattutto come terapia di seconda e terza linea, anche in considerazione dei rischi associati al suo uso [8]. Analogamente, anche ciclofosfamide è stata estesamente usata, seppure come trattamento off-label, per i pazienti con SM a rapida evoluzione, in particolare seguendo la strategia dell'escalation therapy [43].…”
Section: Gli Algoritmi DI Trattamentounclassified
“…Di recente approvazione fra i farmaci di prima linea sono due nuovi farmaci orali, teriflunomide [3] e dimetilfumarato [4], i quali si aggiungono ai noti farmaci iniettivi (interferone beta-1a, beta-1b e glatiramer acetato) di comprovata efficacia e sicurezza [5]. È stato inoltre più recentemente approvato alemtuzumab [6], anticorpo monoclonale umanizzato che trova indicazione per il trattamento di pazienti con forme più aggressive di malattia, e che si aggiunge a fingolimod, natalizumab e mitoxantrone che fino a oggi hanno rappresentato lo scenario farmacologico per i pazienti non-responders alle terapie di prima linea [7,8]. Nel corso degli anni il trattamento della SM si è avvalso anche di farmaci immunosoppressivi tuttora non approvati per questa indicazione e usati off-label, per i quali sono comunque disponibili dati di efficacia e sicurezza ricavati dal loro uso nella pratica clinica quotidiana, fra questi azatioprina, metotrexato, ciclofosfamide [9][10][11].…”
unclassified